Characteristic patterns of HLA presentation and T cell differentiation in adult-onset Still's disease. (27th July 2018) - Jung, Ju-Yang; Choi, Bunsoon; Sayeed, Hasan MD; Suh, Chang-Hee; Kim, Ye Won; Kim, Hyoun-Ah; Sohn, Seonghyang
We examined the expression of human leukocyte antigen (HLA) and composition of differentiated T cells in the peripheral blood to understand the characteristics of the immune changes in patients with adult-onset Still's disease (AOSD). This study enrolled patients with AOSD (n = 14), patients with rheumatoid arthritis (RA, n = 20), and healthy controls (HC, n = 20). The percentage of surface-stained cells with HLA-DP, DQ, and DR alleles and the composition of differentiated T cells in peripheral blood leukocytes (PBLs) were evaluated by flow cytometry. AOSD patients exhibited significantly higher percentages of lymphocytes presenting HLA-DP and HLA-DR, and lower percentages of cells presenting HLA-DQ, than RA patients or HC. The proportions of CD4+, CD4+CCR7+, CD4+CD62L–, and CD8+CD62L– cells from PBLs were decreased in AOSD patients relative to RA patients or HCs. By contrast, AOSD patients had higher proportions of CD8+naïve T cells in whole blood relative to RA patients or HC. The proportions of CD4+ effector memory T cells, CD8+ naïve T cells, and CD8+ effector memory T cells in whole blood cells and CD4+ effector memory T cell in lymphocytes were significantly associated with the systemic score. While the proportions of CD4+, CD8+, CCR7+, CD4+CCR7+, CD4+CD62L–, and CD8+CD62L– cells were significantly decreased in AOSD patients, and the proportion of CD8+naïve T cells was elevated in AOSD and correlated with the systemic score. Further studies of a large cohort of AOSD patients will be necessary to evaluate these markers in the pathogenesis of AOSD.